The art on the lips. About the improvement of speech proficiency with the usage of local art on on-line lessons of Polish as a foreign language - Kownacka, Patrycja (Activation-innovation-inspiration in (glotto) didactics, 2022)
The subject of the article are proposals of usage of local art in the context of improvement of speech proficiency on on-line lessons of Polish as a foreign language on the level B1 and B2. The goal of reflections is to present the activating methods and the tools of gamification to improve the skills of freely speaking about artistic elements existing in the city space and highlights of such approach to the practising of speech. The base material consists the products of art which represent Podlaskie local art: a book “Szeptem” written by Vital Voranau, an exhibition ,,...daj nam dzisiaj” at Arsenał Gallery in Białystok, selected murals, short movie “Franek” directed by Bartek Tryzna and advertising spot of festival “Up to Date Festival”. In the article there are examples of activities, used in order to add dynamization in the educational process in the case of speech proficiency, for example the project of exhibition, modified version of 6 hats’ method, didactic games (tic tac toe) or theatre staging. The end of article shows the reflections about the highlights of usage of local art in the context of didactics of Polish as a foreign language.